Effects of the Catalyst Dynamic Changes and Influence of the Reaction Environment on the Performance of Electrochemical CO2 Reduction - Chen, Jiayi; Wang, Lei (Advanced materials (Weinheim), 2022)
Electrochemical reduction of carbon dioxide (CO2) is substantially researched due to its potential for storing intermittent renewable electricity and simultaneously helping mitigating the pressing CO2 emission concerns. The major challenge of electrochemical CO2 reduction lies on having good controls of this reaction due to its complicated reaction networks and its unusual sensitivity to the dynamic changes of the catalyst structure (chemical states, compositions, facets and morphology, etc.), and to the non‐catalyst components at the electrode/electrolyte interface, in another word the reaction environments. To date, a comprehensive analysis on the interplays between the above catalyst‐dynamic‐changes/reaction environments and the CO2 reduction performance is rare, if not none. In this review, the catalyst dynamic changes observed during the catalysis are discussed based on the recent reports of electrochemical CO2 reduction. Then, the above dynamic changes are correlated to their effects on the catalytic performance. The influences of the reaction environments on the performance of CO2 reduction are also discussed. Finally, some perspectives on future investigations are offered with the aim of understanding the origins of the effects from the catalyst dynamic changes and the reaction environments, which will allow one to better control the CO2 reduction toward the desired products. This review focus on understanding the origin of the dynamic changes at the catalyst–electrolyte interface, and uncovering the interplays between these changes and the CO2 reduction performance, the obtained insights can guide the design of catalysts and reactors for the efficient electrochemical CO2 reduction.